Illustration on Javanese Manuscripts: The Intellectuality and the Capability of Thinking into Indonesian Art and Writing Culture - Adisasmito, Nuning Y. Damayanti (ASPENSI in Bandung, Indonesia, 2010)
ABSTRACT: The tradition of writing and drawing in illustration was found in the old manuscript. Some parts of those old manuscripts show unique illustrations as well as the local identity of Nusantaraâs society. The manuscript reflects the society culture of thinking and aesthetic achievement of visual art. The illustrations of old Javanese manuscripts were well documented and has various representation in visualization art and style, drawing method, theme, and visual objects, even though the visualization of the visual concepts is practically similar to another. It reflects the structured illustration and style as well as expression symbol of the Javanese society in that era. Illustration of the old Javanese manuscript in the colonial era has changed and developed its visual state as the interaction between the Animism in the Pre-Hinduism era, cultural paradigm of Hinduism-Buddhism, Islamic and Colonialism. KEY WORDS: writing tradition, illustration tradition, colonialism, and old Javanese manuscript.About the Author: Dr. Nuning Y. Damayanti Adisasmito is a Lecturer at the Faculty of Fine Art and Design ITB (Bandung Institute of Technology), Jalan Ganesha 10 Bandung, West Java, Indonesia. She can be reached at: aryasena@bdg.centrin.net.idHow to cite this article? Adisasmito, Nuning Y. Damayanti. (2010). âIllustration on Javanese Manuscripts: The Intellectuality and the Capability of Thinking into Indonesian Art and Writing Cultureâ in TAWARIKH: International Journal for Historical Studies, Vol.1(2) April, pp.123-138. Bandung, Indonesia: ASPENSI [Asosiasi Sarjana Pendidikan Sejarah Indonesia], ISSN 2085-0980. Chronicle of the article: Accepted (February 2, 2010); Revised (March 11, 2010); and Published (April 28, 2010).